Digital transformation and the choice of management control modes in enterprise groups. - Junhui Li; Xianzhi Zhang (PLoS ONE)
Digital transformation has a significant impact on the choice of management control modes within enterprise groups. This study uses data from publicly listed companies in China from 2010 to 2022 to empirically examine the effect of digital transformation on the management control modes of enterprise groups. It further explores the mechanism and moderating effects of digital transformation in influencing the selection of management control modes. The findings indicate that, under the impact of digital transformation, enterprise groups are more inclined to adopt decentralized management control modes. The mechanism analysis suggests that digital transformation can mitigate principal-agent problems between parent and subsidiary companies by improving internal control quality, thus promoting a decentralized management control mode. The moderating effects reveal that the facilitative impact of digital transformation on choosing a decentralized control mode is more pronounced in state-owned enterprise groups and those operating in environments with higher uncertainty. Moreover, as the level of digital transformation or corporate governance improves, enterprise groups are more likely to adopt decentralized management control modes. This study extends the measurement indicators for the choice of management control modes in enterprise groups across four dimensions: personnel authority, operational authority, investment authority, and financial authority, and constructs a research framework to reveal the practical effects of China's digital transformation strategy.